Body image in adolescents and its relationship to socio-cultural factors - Doğan, Özcan; Bayhan, Pınar; Yükselen, Arzu; Işıtan, Sonnur (EDAM, 2018)
This study was planned in order to analyze adolescent body image by age and gender, evaluate the relationship between adolescent body image and socio-cultural factors, and determine the extent to which variables such as age, gender, and Body Mass Index (BMI) can serve as predictors of the influential habits and strategies needed to achieve a better level of body satisfaction. Within this context, the data was collected using the following questionnaires: the Body Image and Body Size Variation Questionnaire; the Perceived Socio-Cultural Effects Concerning Body Image and Body Size Questionnaire; and a Data Form containing the demographic data. One thousand two hundred and eighty 7th, 8th, 9th, and 10th grade students were selected for the study using probabilistic, stratified, cluster sampling. The findings show a strong con elation between adolescent body image and socio-cultural factors, as well as between adolescent body image and the importance adolescents place on the media. From the regression analysis conducted using correlated variables, it was demonstrated that body satisfaction, habits and strategies with respect to body-building that pertain to adolescent body image can also be predicted by studying the attitudes and behaviours of the students' parents, peers, and the socio-cultural variables in evidence, such as the perceived effect of the media.
WOS: 000448221200003
Keywords: Adolescent; Body Image in Adolescence; Body Image; Socio Cultural Factors in Adolescents; Media